Transformational Leadership In Public Sector Innovation; Toward An Elderly-Friendly City - Saadah, Maratun (JIAP (Jurnal Ilmu Administrasi Publik), 2023)
The article examines the role of transformational leadership in public sector innovation, specifically in addressing the challenges of managing older people to build an elderly-friendly community. The research focuses on the leadership of Jambi Mayor in employing innovation to realize Jambi as an Elderly-Friendly City. This is a descriptive qualitative study that aims to identify new information related to the transformational leadership of Jambi Mayor in innovating an Elderly-Friendly City. The authors identified transformational leadership as a major style in carrying out innovation. The study found that Jambi City is continuously promoting the importance of creating elderly-friendly cities and communities through the leadership of its Mayor. The study found that transformational leadership practices played a significant role in the process of making Jambi City an Elderly-Friendly City. The mayor motivated civil servants to improve their attitudes and assumptions towards public health services. The research concludes that leadership styles have a direct impact on the level of innovation adopted and the success or failure of strategic responses.